2014
DOI: 10.1080/01494929.2014.905816
|View full text |Cite
|
Sign up to set email alerts
|

Black Men and the Decision to Marry

Abstract: The purpose of this descriptive study is to understand the decision to marry among a sample of 52 married Black men. Qualitative inquiry was used to explore this issue. The men noted five factors that encouraged marriage: wife's characteristics, spirituality, desire to be together, readiness to marry, and encouragement from others. Five barriers to marriage were personal reservations, perceived loss of freedom, disapproval from others, prior relationship experiences, and finances. If they had to make the choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…These findings indicate that an attractive partner permits both genders to obtain new experiences more easily. However, our findings also demonstrate that an attractive partner is a status symbol for men but not women, as shown in some previous studies ( Hurt, 2014 ; Gittins, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings indicate that an attractive partner permits both genders to obtain new experiences more easily. However, our findings also demonstrate that an attractive partner is a status symbol for men but not women, as shown in some previous studies ( Hurt, 2014 ; Gittins, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…These findings may reflect different social norms related to raising families and children. Men may perceive family and children as requiring them to give up some of their interests and care more for others, while women may perceive raising family and children as serving their own interests and the interests of the other ( Buss et al, 2001 ; Hurt, 2014 ; Gittins, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies (Carroll et al, 2009;Karada g, 2006) have reported that more than half of young people did not feel ready for marriage. Marital readiness is regarded a factor facilitating the decision to marry (Hurt, 2014), and it has a positive association with marital satisfaction (Holman et al, 1994). Although marital readiness plays an important role before and during the marriage, Goad (1987) drew attention to the fact that marital readiness is not sufficiently emphasized in studies on marriage and family.…”
mentioning
confidence: 99%